Liquid hot water as sustainable biomass pretreatment technique for bioenergy production: A review. (January 2022) - Chen, Wei-Hsin; Nižetić, Sandro; Sirohi, Ranjna; Huang, Zuohua; Luque, Rafael; M.Papadopoulos, Agis; Sakthivel, R.; Phuong Nguyen, Xuan; Tuan Hoang, Anh
Graphical abstract: Highlights: Lignocellulosic biomass is promising renewable source for bioenergy production. Reaction mechanism and role of LHW in biomass pretreatment are presented in detail. Operating characteristics of various LHW reactors are critically compared. Influencing factors on pretreatment efficiency using LHW are thoroughly analyzed. Techno-economic challenges and prospects of LHW-based pretreatment are discussed. Abstract: In recent years, lignocellulosic biomass has emerged as one of the most versatile energy sources among the research community for the production of biofuels and value-added chemicals. However, biomass pretreatment plays an important role in reducing the recalcitrant properties of lignocellulose, leading to superior quality of target products in bioenergy production. Among existing pretreatment techniques, liquid hot water (LHW) pretreatment has several outstanding advantages compared to others including minimum formation of monomeric sugars, significant removal of hemicellulose, and positive environmental impacts; however, several constraints of LHW pretreatment should be clarified. This contribution aims to provide a comprehensive analysis of reaction mechanism, reactor characteristics, influencing factors, techno-economic aspects, challenges, and prospects for LHW-based biomass pretreatment. Generally, LHW pretreatment could be widely employed in bioenergy processing from biomass, but circular economy-based advanced pretreatment techniques should be further studied in the future to achieve maximum efficiency, and minimum cost and drawbacks.